Unplanned postoperative reintubation following general and vascular surgical procedures: Outcomes and risk factors. (September 2018) - Acheampong, Derrick; Guerrier, Shanice; Lavarias, Valentina; Pechman, David; Mills, Christopher; Inabnet, William; Leitman, I. Michael
Abstract: Background: Unplanned postoperative reintubation (UPR) is a marker for severe adverse outcomes following general and vascular surgery. Study design: A retrospective analysis of 8809 adult patients, aged 18 years and older, who underwent major general and vascular surgery at a large single-center urban hospital was conducted from January 2013 to September 2016. Patients were grouped into those who experienced UPR and those who did not. Univariate and multivariate regression analyses were used to identify predictors of UPR, and association of UPR with adverse postoperative outcomes. All regression models had Hosmer-Lemeshow P > 0.05, and C-statistic >0.75, indicating excellent goodness-of-fit and discrimination. Results: Of the 8809 patients included, 138 (1.6%) experienced UPR. There was no statistical difference in incidence of UPR between general and vascular surgery patients (p = 0.53). Independent predictors of UPR advanced age (OR 5.1, 95%CI 3.5–7.5, p < 0.01), higher ASA status (OR 7.9, 95%CI 5.6–11.1, p < 0.01), CHF (OR 7.0, 95%CI 3.6–13.9, p = 0.02), acute renal failure or dialysis (OR 3.1, 95%CI 1.8–5.7, p = 0.01), weight loss (OR 5.2, 95%CI 2.8–9.6, p = 0.01), systemic sepsis (OR 4.8, 95%CI 3.4–6.9, p < 0.01), elevated preoperative creatinine (OR 4.2, 95%CI 3.0–5.9, p = 0.01), hypoalbuminemia (OR 5.3, 95% CI 3.8–7.5, p = 0.01), and anemia (OR 4.0, 95%CI 2.8–5.9, p < 0.01). Following surgery, UPR was associated with increased mortality (OR 3.8, 95%CI 2.7–5.2, p < 0.01), pulmonary complications (OR 1.8, 95%CI 1.7–2.0, p < 0.01), renal complications (OR 2.6, 95%CI 1.7–3.5, p < 0.01), cardiac complications (OR 4.6, 95%CI 2.0–6.7, p < 0.01), postoperative RBC transfusion (OR 5.7, 95%CI 3.8–8.6, p < 0.01), and prolonged hospitalization (OR 1.8, 95%CI 1.5–2.4, p < 0.01). Conclusion: UPR is significantly associated with postoperative morbidity and mortality. Perioperative management aimed at decreasing incidences of UPR after noncardiac surgery should target preoperative anemia in addition to previously identified predictors. Highlights: Unplanned postoperative reintubation (UPR) is a marker for severe adverse outcome following surgery. UPR following major surgery occurred in 1.6% patients. Patients who required UPR had increased mortality. Underlying risk factors and postoperative complications may be a marker for other severe systemic disease.